A Revolution Or A Journey Towards Liberty? A Cognitive Metaphorical Analysis Of The Jasmine Revolution In English And Arabic News Discourse - Waheed M. A. Altohami (Ijaz Arabi Journal of Arabic Learning, 2022)
This study offers a cognitive metaphorical analysis of the events framing the Tunisian Revolution in English and Arabic news discourse between 2010 and 2014. The study addressed two central questions: (1) How has the Tunisian Revolution been metaphorically represented in English and Arabic political news discourse based on the cognitive domain of journey? What are the similarities and differences between the metaphorical representations in the same news discourse? The conceptual integration network emerging in the analysis is single-scope as the two input spaces of journey and revolution were demonstrated to have different organizing frames. Specifically, only the frame of journey is projected to organize the blend. Findings showed that anchoring the concept of revolution to that of journey has created a kind of semantic tension that helped journalists to evoke emotional responses and manipulate the discursive function of metaphors as persuasive tools. Because of the cross-space mappings between journey and revolution, nearly all concepts related to the revolutionary experience proved to have a counterpart in the journey frame. Equally important, the results of comparing and contrasting cognitive metaphors in English and Arabic news discourse could offer insights into the way language develops based on a cognitive basis. Therefore, learners of both English and Arabic could access the system governing language learning concerning the formation of semantic networks based on different conceptual frames, thereby enhancing their metaphorical competence. Developing learners’ metaphorical competence would help them in analyzing, reconstructing, and translating diverse textual data